PENGARUH PENGANGGARAN PARTISIPATIF, SISTEM PENGUKURAN KINERJA DAN KOMPENSASI INSENTIF TERHADAP KINERJA MANAJERIAL PADA PERBANKAN DI BANDA ACEH - Syahrul Maulidi, Hasan Basri, Nurdasila (Jurnal Akuntansi, 2017)
Abstract : managerial performance is one factor that is used to improve organizational effectiveness. managerial performance is said to be effective if the goal of participatory budgeting, performance measurement and incentive compensation is reached. this study aimed to examine the influence of participatory budgeting, performance measurement systems, and incentive compensation to managerial performance of banks in banda aceh. it examine the influence of participatory budgeting on managerial performance, test the effect of the performance measurement system on managerial performance, and examine the effect of incentive compensation to managerial performance. this study uses multiple linear regression analysis with 30 participants. the results showed that participatory budgeting, performance measurement and incentive compensation simultaneously influence the performance of management on banking in banda aceh, participatory budgeting influences managerial performance in banking in banda aceh, performance measurement systems influences the managerial performance of banking in banda aceh, performance measurement system influence on managerial performance banking in banda aceh and the incentive compensation effect on managerial performance banking in banda aceh.Keywords: Participatory Budgeting, Performance Measurement System, Incentive Compensation, Managerial Performance  Abstrak : Kinerja manajerial merupakan salah satu faktor yang digunakan untuk meningkatkan efektivitas organisasi. Kinerja manajerial dikatakan efektif jika tujuan penganggaran partisipatif, sistem pengukuran kinerja dan kompensasi insentif tercapai. Penelitian ini bertujuan untuk menguji pengaruh penganggaran partisipatif, sistem pengukuran kinerja, kompensasi insentif terhadap kinerja manajerial pada perbankan di Banda Aceh. Penelitian ini menggunakan analisis regresi linear berganda pada responden yang berjumlah 30 orang. Hasil penelitian menunjukkan bahwa penganggaran partisipatif, sistem pengukuran kinerja dan kompensasi insentif secara bersama-sama berpengaruh terhadap kinerja manajerial pada Perbankan di Banda Aceh. Penganggaran partisipatif berpengaruh terhadap kinerja manajerial pada Perbankan di Banda Aceh. Sistem pengukuran kinerja berpengaruh terhadap kinerja manajerial pada Perbankan di Banda Aceh. dan kompensasi insentif berpengaruh terhadap kinerja manajerial pada Perbankan di Banda Aceh.Kata kunci : penganggaran partisipatif, sistem pengukuran kinerja, kompensasi insentif, kinerja manajerial